2012
DOI: 10.1146/annurev-food-022811-101306
|View full text |Cite
|
Sign up to set email alerts
|

X-Ray Irradiation as a Microbial Intervention Strategy for Food

Abstract: First recognized in 1895, X-ray irradiation soon became a breakthrough diagnostic tool for the dental and medical professions. However, the food industry remained slow to adopt X-ray irradiation as a means for controlling insects and microbial contaminants in food, instead using gamma and electron beam (E-beam) irradiation. However, the reinvention of X-ray machines with increased efficiency, combined with recent developments in legislation and engineering, is now allowing X-ray to actively compete with gamma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(18 citation statements)
references
References 76 publications
0
16
0
1
Order By: Relevance
“…During irradiation, the dose, the food composition and the type of microorganism affect differently the efficacy of treatment (Moosekian et al, 2012). In general, the irradiation dose is positively proportional to the degree of killing microorganisms.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…During irradiation, the dose, the food composition and the type of microorganism affect differently the efficacy of treatment (Moosekian et al, 2012). In general, the irradiation dose is positively proportional to the degree of killing microorganisms.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…When the food properties are adverse to microbial growth, their resistance to the radiation is reduced and can be killed by low irradiation doses. Regarding microorganisms, they show different tolerance levels towards specific doses of irradiation; normally, Gram-positive bacteria display stronger resistance than Gram-negative bacteria, while prokaryotic microorganisms are more resistant than eukaryotic microorganisms (Moosekian et al, 2012).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Rather, the public has received information about from mixed sources. Negative perceptions of FI among the public were engendered by the wide dissemination of information from opposed special interest groups . Studies showed that being adequately informed about the processes, safety and benefits of FI translated into greater public acceptance of this technology .…”
Section: Awareness and Knowledgementioning
confidence: 99%
“…Negative perceptions of FI among the public were engendered by the wide dissemination of information from opposed special interest groups . Studies showed that being adequately informed about the processes, safety and benefits of FI translated into greater public acceptance of this technology . Calls were made for a co‐ordinated, balanced public education and information programme , to raise public awareness of the benefits, costs and risks of FI .…”
Section: Awareness and Knowledgementioning
confidence: 99%
“…1,2 Soğuk pastörizasyon olarak da isimlendirilen bu teknolojiyle besin kaynaklı hastalıkların önlenmesi, besinlerin dayanıklılıklarının artırılması, böcek kontrolü, filizlenmenin ve olgunlaşmanın geciktirilmesi, sterilizasyon ve raf ömrünün uzatılması gibi birçok amaca hizmet etmektedir. [2][3][4][5][6][7][8][9] İyonize edici ışınların canlı organizmalar üzerine etkisi konusundaki araştırmalar 20.yy'ın başlarında gelişmeye başlamış, ilk patent 1905 yılında alınmıştır ve ilk kez 1930 yılında besinlerde kullanılmaya başlanmıştır. 11 Alınan ilk patentle; radyoaktif gama ışınlarının özellikle tahıllar olmak üzere besinlerin katkı maddeleri ilave edilmeden uzun süre bozulmadan saklanabilecekleri ileri sürülmüştür.…”
Section: Introductionunclassified